Variable stem-final fricative voicing in American English plurals: Different pa[ð θ]s of change. (22nd October 2018) - MacKenzie, Laurel
Abstract: This paper investigates analogical leveling in a small set of English nouns that have irregular plural forms. In these nouns, all of which end in a voiceless fricative, the fricative standardly voices in the plural (e.g., wolf – wol[v]es, path – pa[ð]s, house – hou[z]es ). Using audio data from three large spoken corpora of American English, I demonstrate that this stem-final fricative voicing is variable and conditioned by a number of factors, most notably the identity of the stem-final fricative—with /f/-final lexemes (e.g., wolf ), /θ/-final lexemes (e.g., path ), and the /s/-final lexeme house all patterning differently in apparent time—and the frequency of a lexeme in its plural form. I argue that the way these two factors affect the variation is reminiscent of the patterns seen in children's first language acquisition errors, providing a potential source for the variation and underscoring the importance of considering morphophonological factors when accounting for patterns of change.